Meretas Konsep Baru Pidana Denda terhadap Tindak Pidana Korupsi: Analisis Komparatif dengan Foreign Corrupt Practices Act Amerika Serikat, Bribery Act Inggris, dan Wetboek van Strafrecht Belanda - Valerian, Dion (Integritas: Jurnal Antikorupsi, 2019)
Indonesian Anti-Corruption Act stipulates its criminal fines provision by determining a fixed amount of fines in its criminal offences’ formulation. This article analyses and compares the concept of criminal fines in the Indonesian Anti-Corruption Act, United States Foreign Corrupt Practices Act, United Kingdom Bribery Act, and Dutch Criminal Code. The study found that each of the aforementioned US, UK, and Dutch anti-bribery laws has its own distinctive concept to overcome the problem of criminal fines provision’s stringency, that could be used in Indonesian Anti-Corruption Act reform.